1973
DOI: 10.1007/bf00388580
|View full text |Cite
|
Sign up to set email alerts
|

Experimental control of the activity of the quiescent centre in excised root tips of Zea mays

Abstract: Quiescent centres have been demonstrated in cultured excised root tips of both Pisum sativum and Zea mays. Upon addition of sucrose to Zea roots which have been deprived of carbohydrate, the cells of the quiescent zone as well as those of the rest of the meristem undergo DNA synthesis. Following the onset of proliferative activity in the meristem, DNA synthesis in the quiescent-centre cells is again arrested. It is suggested that the dividing cells of the meristem are responsible for the maintenance of the qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1974
1974
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…The second approach demonstrated that inhibition of DNA synthesis lowered steady-state levels of H2A mRNA and showed that its expression was replication dependent. Furthermore, we could not detect any expression of H2A mRNA in the root quiescent center, which is known for its very slow cell division rates in all angiosperm roots studied (Webster and Langenauer, 1973;Clowes, 1975), nor in noncycling, mature root tissues. This could not be attributed to the lack of sensitivity to H2A mRNA, since low to moderate levels of mRNA are detectable by standard colorimetric techniques used with the DIG-labeling protocol (Kiyama et al, 1990;Tanimoto and Rost, 1993).…”
Section: Replication-dependent Expression Of H2a Mrnamentioning
confidence: 75%
“…The second approach demonstrated that inhibition of DNA synthesis lowered steady-state levels of H2A mRNA and showed that its expression was replication dependent. Furthermore, we could not detect any expression of H2A mRNA in the root quiescent center, which is known for its very slow cell division rates in all angiosperm roots studied (Webster and Langenauer, 1973;Clowes, 1975), nor in noncycling, mature root tissues. This could not be attributed to the lack of sensitivity to H2A mRNA, since low to moderate levels of mRNA are detectable by standard colorimetric techniques used with the DIG-labeling protocol (Kiyama et al, 1990;Tanimoto and Rost, 1993).…”
Section: Replication-dependent Expression Of H2a Mrnamentioning
confidence: 75%
“…In both plants fast cycling cells exist side by side with non-cycling cells in the stele and slow cycling cells exist with non-cycling cells in the quiescent centre, but DNA builds up in at least some of the stelar cells after cycling has ended. There is no evidence from either plant grown in this laboratory for the cycling cells of the quiescent centre being confined to a particular sub-region as Webster and Langenauer (1973) reported for another cultivar of Zea.…”
Section: Discussionmentioning
confidence: 52%
“…It has been determined that cells of the root quiescent centre can be induced to undergo greatly increased DNA synthesis and mitotic activity by treatments which arrest growth and subsequently allow it to proceed (Clowes and Stewart 1967;Webster and Langenauer 1973;Langenauer et al 1974). The work that bears most directly upon the present investigation is that of Clowes and Stewart (1967) in which young seedlings of Zea mays were put into a dormant state by exposure to low temperature and subsequently were restored to active growth by a return to normal temperature.…”
Section: Discussionmentioning
confidence: 93%
“…Clowes and Stewart (1967) have reported activity in the quiescent centre of seedling roots of Zea after a cold-induced period of dormancy. Finally, it has been shown that in cultured roots in which cell proliferation in the meristem has been arrested by carbohydrate starvation, DNA synthesis occurs in the quiescent centre when carbohydrate is added to the culture medium (Webster and Langenauer 1973;Langenauer et al 1974).…”
Section: Introductionmentioning
confidence: 99%